Pendidikan Politik di Perguruan Tinggi : Sebuah Konsepsi - Imam Alfikri Pratama (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
As an effort, political education becomes an investment in sustainable democracy. The result is citizens’ political awareness and active involvement democratically in national matters. With an opportunity of demographic bonus in the future, the best political therapy must be implemented to young people as a guarantee of the well-functioning of democracy, in which some of them are higher education students. Political education in higher education is constructed in both formal and non-formal forms. In the formal form, it is carried out through political teaching, while the non-formal form is related to the way individuals summarize political knowledge through reflection on a political system. It can be carried out together between teaching through Pancasila and Citizenship Education in the curricular domain and social learning through student organizations in the non-curricular domain.